Multi-Biomarker Oxidative Stress Panel Improves Prediction of Perinatal and Postpartum Outcomes in Gestational Diabetes: A Prospective Study - Raffik, Daroon Essam; Mohammed , Batool Khalil; Shawkat , Zainab Adnan (American Journal of Bioscience and Clinical Integrity, 2025)
Hyperglycemia and insulin resistance lead to elevated oxidative stress in 14% of pregnancies worldwide, which is known as gestational diabetes mellitus (GDM). Existing biomarker methods are still restricted. The goal is to find out how well a full panel of oxidative stress biomarkers predicts postpartum glucose tolerance and perinatal outcomes in patients with GDM. Strategies: prospective case-control study of 150 pregnant women (75 GDM, 75 controls) at 24-28 weeks gestation. GDM was identified based on IADPSG criteria. Biomarkers analyzed included ischemia-modified albumin (IMA), total oxidant status (TOS), total antioxidant status (TAS), malondialdehyde (MDA), glutathione (GSH), and catalase (CAT). Multivariate analysis adjusted for confounders. At six to twelve weeks, postpartum OGTT is conducted. The following oxidative markers were considerably higher GDM patients: MDA (4.8±1.2 vs 2.9±0.8 nmol/mL), TOS (28.4±6.2 vs 18.7±4.1 μmol H₂O₂ Eq/L), and IMA (0.89±0.12 vs 0.65±0.08 ABSU) (all p<0.001). GSH (285±45 vs 365±52 μmol/L), CAT (42.8±8.5 vs 58.2±9.7 U/mg protein), and TAS (1.24±0.18 vs 1.58±0.23 mmol Trolox Eq/L) all showed decreased antioxidant ability (all p<0.001). infants with elevated MDA (OR 1.89) and TOS (OR 2.34) were predicted to be big for gestational age. GSH (AUC 0.72) was lower and prenatal MDA (AUC 0.78) was higher, which indicated postpartum glucose intolerance. Conclusions: Beyond a single biomarker, GDM entails a total oxidative imbalance. Improved screening methods for better maternal-fetal outcomes are supported by multi-dimensional biomarker panels, which offer superior risk assessment for perinatal problems and postpartum metabolic dysfunction.